Hysteresis behavior of traditional timber structures by full-scale tests. Issue 2 (January 2018) - Chen, Jinyong; Chen, Yohchia Frank; Shi, Xiwang; Zhao, Yanxia; Li, Tieying
To study the seismic response of a traditional timber structure in China, a full-scale model capturing the main characteristics of a representative ancient Chinese wooden structure in Song Dynasty (960–1279 AD) was established and tested considering three different levels of vertical loads, which is one-story sophisticated timber structure consisting of four columns and Dou - gon g sets. A swing column was used to apply the synchronous horizontal force. Tests under the low-cyclic loading were performed considering three levels of vertical load to reveal the hysteretic behavior of the historic buildings. Based on the observed characteristics from restoring forces, the ancient wooden structure appears to have a good ductility despite of its low inherent energy dissipation capability. Based on the test results, the following relationships are established: loads versus displacements with key turning points, the loads at the key points versus the roof weights, the displacements at the key points with the column diameter, and structural stiffness versus ductility. Finally, a limiting value of drift angle for structural design and the equivalent viscous damping and ductility factor for dynamical response analysis are proposed.